Reliability and validity of the Chester Step Test in people with Interstitial Lung Disease - Alves, Ana (2022)
The Chester Step Test (CST) requires minimal physical space to assess exercise tolerance, making it suitable to be used in most settings. However, its clinimetric properties in people with interstitial lung diseases (ILD) are unknown. We therefore assessed the reliability and validity of the CST in people with ILD. A cross-sectional study was conducted. First, a CST-1 and a 6-minute walk test (6MWT) were performed. After 48-72 hours, a CST-2 was repeated. A 2nd rater was present in one of the sessions. Relative reliability was measured using intraclass correlation coefficient (ICC1,1 and ICC2,1). Absolute reliability was determined using standard error of measurement (SEM), minimal detectable change at 95% confidence interval (MDC95) and the Bland&Altman method. Construct validity was explored using Spearman correlation coefficient (rs) between the number of steps taken in the best CST and the distance covered in 6MWT. 66 patients with ILD (66±13 years; 49%men; FVC 79±19pp; DLCO 49±18pp) participated. Relative (ICC 0.95-1.0) and absolute reliability were excellent without evidence of systematic bias (Figure 1). The SEM and MDC95 were 11.8 and 32.6 steps, respectively. The correlation between CST and 6MWT was significant, positive and high (rs=0.85, p=0.00). The CST is a reliable and valid test to evaluate exercise tolerance in people with ILD.